Starry sky appearance of tuberculoma - Nigam, Nehil; Kela, Gunjan (International Journal of Contemporary Pediatrics, 2020)
CNS tuberculosis accounts for only 10% of all cases of tuberculosis, carries a high mortality and morbidity. Tuberculoma of the brain is an important clinical entity. The main challenge in the management of brain tuberculoma is its diagnosis. Hereby, referring case of a 12 years old male child who presented with clinical picture of tuberculosis but radiologically NCC, hence posing a diagnostic dilemma as clinically it was in the favor of tuberculosis whereas radiologically inclination was towards neurocysticercosis. Based on clinical manifestations it was suggestive of meningitis, CSF picture was suggestive of hypoglycorrhachia. CT chest showed miliary pattern and neuroimaging showing multiple ring enhancing lesions. High index of clinical suspicion is required to make a diagnosis and evaluation with reports.